Deliberative democracy for diabolical times confronting populism, extremism, denial, and authoritarianism - Bächtiger, André 1971-; Dryzek, John S. 1953- (Cambridge University Press, 2024)
Democracy today faces deep and complex challenges, especially when it comes to political communication and the quality of public discourse. Dishonest and manipulative communication amplified by unscrupulous politicians and media pervades these diabolical times, enabling right-wing populism, extremism, truth denial, and authoritarianism to flourish. To tackle these issues, we need to encourage meaningful deliberative communication - creating spaces for reflective and constructive dialogue, repairing unhealthy public spheres while preserving healthier ones, and building discursive bridges across deep divides. Citizens who see through elite manipulations should be at the core of this response, especially if bad elite behavior is to be effectively constrained. Democratic activists and leaders, diverse interpersonal networks, resilient public spheres, deliberative innovations and clever communication strategies all have vital roles to play in both defending and renewing democracy. Healthy discursive infrastructures can make democracies work again
Title from publisher's bibliographic system (viewed on 28 Mar 2024)
An introduction for diabolical times -- Deliberation for realists and skeptics -- Democracy in a diabolical soundscape -- How to deliberate with (and against) populists -- How to deliberate with (and against) extremists -- How to deliberate with (and against) deniers -- How to deliberate with (and against) authoritarians -- How to deliberate with everybody -- How to renew a deliberative democracy
Keywords: Deliberative democracy; Political participation